The evaluation of the repeatability of the 13C-ketoisocaproate breath test for assessing hepatic mitochondrial function. Issue 2 (4th March 2019) - Afolabi, Paul R.; Scorletti, Eleonora; Calder, Philip C.; Byrne, Christopher D.
ABSTRACT: The 13 C-ketoisocaproate ( 13 C-KICA) breath test (BT) has been recently proposed as a non-invasive test for assessing hepatic mitochondrial function. Results of the 13 C-KICA BT can be expressed as different parameters. However, the best parameter for expressing the 13 C-KICA BT result is uncertain which hinders use of the BT in routine clinical practice. We have investigated the repeatability of different parameters of 13 C-KICA BT. Thirteen healthy adult subjects (5 men and 8 women) underwent a 13 C-KICA BT on two occasions separated by a gap of approximately 30 days. There were no significant differences between the repeated measurements for all the test parameters over 30 days. Furthermore, the Bland Altman statistics showed no fixed or proportional bias for any of the test parameters. The cumulative 13 C-dose enrichment over 60 min had the lowest within-subject variability of 12% compared to all other test parameters. The cumulative 13 C-dose enrichment over 60 min could be a very useful parameter for the 13 C-KICA BT to detect impaired hepatic mitochondrial function in patients with chronic liver diseases.